Coating of Light Fabrics using Polyvinyl Chloride (PVC) and Comparing their Properties to Ordinary Heavy Tent Fabrics - Babiker, M.; El Arabi, S. M. (Gezira Journal of Engineering and Applied Sciences, 2018)
Tents are being widely used in different and diverse applications. They are normally made of woven fabrics having special characteristics to meet the requirements of the end-uses. The usually used woven fabrics result in heavy Tents which face some problems of erection and handling. PVC coating is a technique that can be utilized to improve some properties of the fabrics specially water repellency because it is one of the important properties in tent fabrics. In this work, light weight fabrics were coated using PVC and tested for their mechanical and chemical properties to possibly know their suitability for tents. These properties were compared to those of the heavy weight fabrics which are normally being used for tents. The comparison had shown that the light fabrics coated by PVC weighing 60% of their weight can possibly replace the heavy fabrics in making tents because the coating had improved the properties.